Revolutionary effects of new information technologies - Gerard J. van den Berg (Institute for the Study of Labor (IZA), 2005)
In markets with imperfect information and heterogeneity, the information technology affects the rate at which agents meet, which in turn affects the distribution of production technologies across firms. We show that in models for such markets there are typically multiple equilibria because reservation utility levels and the lowest production technology in use affect each other. The adoption of novel information technologies may then entail a revolution in the sense of a move from an inefficient to an efficient equilibrium. Inefficient production technologies are removed even in sectors where the new information technology has only recently been introduced. The effect is much larger than a marginal comparative-statics effect on a given equilibrium. The results apply to markets for consumer products, labor, intermediate goods, and (public) institutional services,
Keywords: D43; D83; L11; L15; O33; J42; L86; 330; imperfect information; heterogeneity; production technology; informational frictions; Informationstechnik; Unvollkommene Information; Fertigungstechnik; Preiswettbewerb; Agency Theory; Informationstechnik; Unvollkommene Information; Fertigungstechnik; Preiswettbewerb; Agency Theory